Assessment of energy saving potential and lighting system in teaching building - Awang, Mariah; C.S, Tham; Mohd Basir Ruddin, Nurhanis; Abdul Rahman, Mohamad Ashraf; Hamidon, Nuramidah; Ahmad, Faridahanim; Musa, Kamaruzaman; Nagapan, Sasitharan; Abdul Rahman, Mohd Shahril (Penerbit Akademia Baru, 2020)
Energy consumption and the potential for energy savings had become more intensive in public buildings in order to improve energy performance. This case study was identified the current occupancy, lighting use patterns and lighting performance in G3 Block B teaching building where most of the teaching rooms were located in University Tun Hussein Onn Malaysia. In order to determine the energy saving potential and strategies for lighting system in the building, a series of data collection were conducted to the effects of occupancy and lighting use patterns to display the lighting energy consumption and lighting energy waste of the case study building. The findings of this study displayed lighting use patterns varied among all the investigated lecture rooms at which 31% of lighting load was wasted and 13% of lighting load misused by the building users were recorded. Moreover, the result of lighting performance of the lecture room obtained was met the recommended average illuminance level (300-500 lux) of lighting for working interiors as classroom in MS 1525:2007. In addition, the perception, awareness and practices of energy conservation behavior on lighting of the building user were also studied through structured questionnaire. With regard to the findings of questionnaire in this study, the responses indicated that most of the respondents agreed they were at good perception, awareness and practices on their energy conservation behavior on lighting. Based on the various data obtained in this project, the energy and cost saving potential strategies were suggested for instances the structural energy conservation measures and non-structural energy conservation measures to improve the usage and efficiency of the lighting system in the teaching building towards energy conservation.